Characterization of hydrogel blending biochar derived from rice husk (RH) and fly ash - Mohd Shukry, Nurul Shazviena (2017)
In the industrial field, the application of biochar is significant for the adsorption process in order to maintain a good condition of environment from any pollutants such as industrial wastewaters and acidic gas which contained organics, chemical and heavy metals. The production of hydrogel biochar derived from rice husk (RH) and fly ash (FA) is a new invention to explore the effectiveness of gas adsorption by characterization using different analysis. Slow paralysis method is practiced in the biochar production due to low heating value and long residence time at 450°C. The hydrogel biochar is produce by using the Acrylamide (AAM) as monomer, N,N’methylenebisacrylamide (MBA) as the cross-linking material and Ammonium Persulphate (APS) as the initiator for hydrogel preparation. The characteristic of the hydrogel biochar samples are determined and analyzed by using the Brunauer-Emmet-Teller (BET) Surface Area, Thermogravimetric Analyzer (TGA) and Field Emission Scanning Electronic Microscope (FESEM) at different ratios of rice husk and fly ash. In the BET analysis, the best sample which present the large surface area of the pores among the others is belongs to the ratio of 50:50 hydrogel biochar derived from Rice Husk and Fly Ash (RH:FA) which had recorded the size of 1.4676 m²/g. Moreover, the results is supported by the TGA analysis which also proves that the 50:50 ratio of hydrogel biochar derived from RH:FA contained the highest percentage of fixed carbon content which is 30.7698% and lowest ash production at 35.0450%. Therefore, the sample of 50:50 RH:FA had been chosen for further analysis by using FESEM to measure the diameter of the pores on the surface of the hydrogel biochar and pore distribution. Thus, as conclusion of the experiment, the optimum and suitable ratio for hydrogel biochar production derived from rice husk and fly ash (RH:FA) is shown by the ratio of 50:50 of hydrogel blending which believed able to act as adsorbent in order to minimize the level of pollution.